Agrobacterium-mediated Genetic Transformation of Rice var. BRRI Dhan 58 (Plant Tissue Culture and Biotechnology, 2021)
Agrobacterium mediated genetic transformation of BRRI Dhan 58 was conducted by using immature embryos following indirect regeneration. High percentage of callus induction at 96.5% was obtained when seeds of BRRI dhan 58 were cultured on modified MS medium supplemented with 2.5 mg/l 2, 4-D under dark condition. The maximum regeneration response was rerecorded when MS was supplemented with 3 mg/l BAP + 0.5 mg/l NAA and 1.0 mg/l Kn. Genetic transformation was performed using A. tumefaciens strain LBA4404 harboring pCAMBIA1301 plasmid carrying the marker genes for β-glucuronidase (GUS) and hygromycin resistance (hptII). Integration of the GUS gene into the genome of the rice plants was confirmed by PCR. The leaf segments of the PCR positive transformed plants showed the expression of GUS. The results of this study would be an effective tool for crop improvement and functional studies of gene on rice plant.Plant Tissue Cult. & Biotech. 31(1): 71-80, 2021 (June)